INTERNAL CONTROL AS AN INSTRUMENT OF SUPPORT RISK MANAGEMENT TO BUSINESS PLAN - Boškov, Veronika (International Journal of Economic Practice and Policy, 2017)
Companies today operate in a very turbulent circumstances. They are exposed to complex influences to which they must act to protect themselves and survive. Risk exposure must be factor into their calculations when creating a business plan but also they must count on it during its implementation. Internal control isexceptionally important because only timely identification of problems and timely action can amortize risk situations. Considering that the business plan includes all planned steps towards realization of business ideas changes and aberrations at any stage have implications for the final result.
Keywords: business plan; risk; RISK MANAGEMENT; accountability